Analisis Hubungan Antar Manusia terhadap Kinerja Karyawan - Abdul Latief; Dhian Rosalina; Devi Apiska (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the effect of human relations on the performance of PT Perkebunan Limbang's employees. This research is a type of descriptive quantitative research with a sample of 134 respondents. The sampling technique in this study uses Probability Sampling and sample determination is done by random sampling. The data analysis method used is simple linear regression analysis. Hypothesis testing is done through partial tests (t test) and test coefficient of determination (R2). The results of the regression equation obtained Y = 2.687 + 0.375X1. The value of constant is 2.687 is the value of employee performance before it is influenced by relationships between humans. increased by 0.375. Relations between humans have a positive and significant effect on the performance of employees at PT Perkebunan Limbang with the results of the t test which is the value of tcount> ttable (5.573> 1.656) and the value of t sig is 0.000 <0.05. The coefficient of determination (R2) is 0.19 0 or 19.0%. This shows the variable relations between humans affect the performance of employees at PT. Weighing Langsa Plantation is 19.0%, and the remaining 81.0% is influenced by other variables not examined in this study, such as motivation and compensation.